Creating Stories by Student Teachers as a Space for Multifaceted Adult Learning. Sustainable and Intercultural Perspective - Aneta Rogalska-Marasińska (Studia z Teorii Wychowania)
The paper discusses the participation of the “Quality Education” goal of SDGs, “Personal, social, and learning to learn competence” of the EU Key Competences for Lifelong Learning, and four categories (the educator is someone who…) of the Competences for Educators in ESD in student teacher university training. It presents the theoretical explorations of relevant content to show possible options to be introduced to pre-service teacher training. Reflections about desired changes in personal and professional development are followed by the presentation of workshop outcomes realised with students of 3rd stage studies of pedagogy at the University of Lodz. Students have been developing their intercultural and sustainable development competences by creating stories with multicultural aspect and sustainable perspective. The paper refers to the application of the author's original learning method “Me and you towards sustainability” inspired by books of Robbins, What if? … (2008, 2018). The paper concludes that learning by creation gives more chances to understand oneself and Others.